Analysis of the impact of people's business credit (KUR) on the economic performance of debtors - Khabibi, Akhmad; Sigit, Tri Angga (Educoretax, 2025)
Micro, Small, and Medium Enterprises (MSMEs) constitute the backbone of the national economy but often face constraints in accessing financing. Since 2007, the People’s Business Credit (Kredit Usaha Rakyat, KUR) program has been designed to expand MSME financial inclusion through affordable loan interest rates and a broad distribution network. This study analyzes the impact of KUR on borrowers’ economic performance using a quantitative one-group pretest–posttest design. Primary data were collected to capture conditions before and after financing within a one-year observation window. Paired difference tests (Paired t-test/Wilcoxon) were applied according to data distribution. The results show significant increases in revenue (+17.10%), profit (+16.27%), and employment (+22.22%). These findings confirm the effectiveness of KUR in enhancing business productivity and income dimensions, although its social effects remain limited. Policy measures that promote business mentoring and financial literacy are recommended to extend KUR’s benefits toward transforming MSME business models.